2012
DOI: 10.4103/0970-4388.105012
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study on the microbial adhesion to preveneered and stainless steel crowns

Abstract: The adhesion of S. mutans to preveneered crowns was higher than to SSC. Full mouth rehabilitation led to significant decrease in S. mutans count in the short term. An increase in S. mutans counts is associated with an increase in OHI-S and GI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…On the other hand, these results disagree with Subramanyam D, et al (13) when evaluate microbial adhesion between two commercially types of SSCs in primary molars and concluded that There was no statistically significant difference seen in the microbial count between the 3M and Kids crown and natural teeth however the drawback of this study was short duration of follow up (1 week). According to Bin AlShaibah W. et al (11) who evaluate the adhesion of Streptococcus mutans to preveneered and stainless-steel crowns and reported that adhesion of S. mutans to preveneered crowns was higher than to SSC and attributed these results due to surface properties of composite which used as veneer such as chemical composition, surface free energy, and surface roughness enhance microbial adhesion.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, these results disagree with Subramanyam D, et al (13) when evaluate microbial adhesion between two commercially types of SSCs in primary molars and concluded that There was no statistically significant difference seen in the microbial count between the 3M and Kids crown and natural teeth however the drawback of this study was short duration of follow up (1 week). According to Bin AlShaibah W. et al (11) who evaluate the adhesion of Streptococcus mutans to preveneered and stainless-steel crowns and reported that adhesion of S. mutans to preveneered crowns was higher than to SSC and attributed these results due to surface properties of composite which used as veneer such as chemical composition, surface free energy, and surface roughness enhance microbial adhesion.…”
Section: Discussionmentioning
confidence: 99%
“…The swabs were collected before preparation of crowns, 1 month and 3 months after cementation (11) . Swabs were taken from occlusal and buccal surface by means of the tips of sterile cottons (12,13) .…”
Section: Microbiological Analysismentioning
confidence: 99%
“…Hence, the appropriate marginal adaptation to the tooth and a reduced discrepancy beyond the CEJ is essential. The SSC has a highly polished surface that limits bacterial adhesion and biofilm formation [ 50 ]. It is, therefore, effective in patients with special needs where routine oral hygiene is impaired [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…An increase in S. mutans counts is associated with an increase in OHI-S and GI. Therefore, parents are advised to supervise oral hygiene care habits for children under the age of 6 [6].…”
Section: Overviewmentioning
confidence: 99%
“…In common, the esthetic approaches comprise SSCs and esthetic resin material combinations. The combinations have raised not only some concerns in terms of both human health and environment but also have sometimes provided unsatisfactory resolutions for parents [5,6]. Thus, researches have inclined the development of metal free esthetic restorations.…”
Section: Overviewmentioning
confidence: 99%